2002
DOI: 10.1046/j.1463-1326.2002.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Nateglinide improves glycaemic control when added to metformin monotherapy: results of a randomized trial with type 2 diabetes patients

Abstract: In patients stabilized on high-dose metformin, the addition of nateglinide improved glycaemic control. The combination of these agents was well tolerated and both doses of nateglinide proved effective. The efficacy of nateglinide 60 mg and the low rate of hypoglycaemia observed at this dose make it suitable for patients close to their therapeutic target on metformin monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
3
36
1
1
Order By: Relevance
“…The association of nateglinide and metformin has already been proven to be an efficacious and safe antidiabetic strategy in type 2 diabetic patients (48). Its What is more specific in our study is the observation that the nateglinide-treated patients showed a significant reduc-F i g u r e 3 .…”
Section: O F T H E S T U D Y I N Gl I B E N C L a Mi D E Gr O U Pmentioning
confidence: 53%
“…The association of nateglinide and metformin has already been proven to be an efficacious and safe antidiabetic strategy in type 2 diabetic patients (48). Its What is more specific in our study is the observation that the nateglinide-treated patients showed a significant reduc-F i g u r e 3 .…”
Section: O F T H E S T U D Y I N Gl I B E N C L a Mi D E Gr O U Pmentioning
confidence: 53%
“…2). The additive effects of nateglinide and metformin in combination were further confirmed in a trial of 467 patients with inadequate glycaemic control, after dietary intervention (HbA 1c 6.8-11%) and despite receiving maximal metformin dosages (≥1.5 g/day) [37]. Nateglinide (60 or 120 mg before main meals) dose-dependently reduced HbA 1c with the greatest reduction being observed in patients with the highest baseline values of HbA 1c (Fig.…”
Section: New Approaches To Combination Therapymentioning
confidence: 64%
“…These agents act directly on pancreatic beta cells to stimulate insulin release and reduce postprandial hyperglycaemia [34,35,36,37,38]. Their mode of action is complementary to agents that target insulin resistance.…”
Section: New Approaches To Combination Therapymentioning
confidence: 99%
“…The glucose-lowering extent of metformin is additive when used in combination with a sulphonylurea, [28][29][30][31][32][33][34] a meglitinide, 35 a thiazolidinedione [36][37][38][39][40][41][42][43][44][45] or an α-glucosidase inhibitor. 20,[46][47][48] A one-year study demonstrated equivalent antihyperglycaemic efficacy with a metformin-sulphonylurea combination compared with a pioglitazone-sulphonylurea combination in patients inadequately controlled on a sulphonylurea alone.…”
Section: Metformin In Combinationmentioning
confidence: 99%